Modulation of cardiac resident macrophages immunometabolism upon high-fat-diet feeding in mice - Zhu, Simeng; Liu, Yujia; Xia, Guofang; Wang, Xiaoqing; Du, Ailian; Wu, Jin; Wang, Yanpeng; Wang, Yuanlong; Shen, Chengxing; Wei, Peng; Xu, Congfeng (Frontiers in Immunology, 2024)
Background A high-fat diet (HFD) contributes to various metabolic disorders and obesity, which are major contributors to cardiovascular disease. As an essential regulator for heart homeostasis, cardiac resident macrophages may go awry and contribute to cardiac pathophysiology upon HFD. Thus, to better understand how HFD induced cardiac dysfunction, this study intends to explore the transcriptional and functional changes in cardiac resident macrophages of HFD mice. Methods C57BL/6J female mice that were 6 weeks old were fed with HFD or normal chow diet (NCD) for 16 weeks. After an evaluation of cardiac functions by echocardiography, mouse hearts were harvested and cardiac resident CCR2- macrophages were sorted, followed by Smart sequencing. Bioinformatics analysis including GO, KEGG, and GSEA analyses were employed to elucidate transcriptional and functional changes. Results Hyperlipidemia and obesity were observed easily upon HFD. The mouse hearts also displayed more severe fibrosis and diastolic dysfunction in HFD mice. Smart sequencing and functional analysis revealed metabolic dysfunctions, especially lipid-related genes and pathways. Besides this, antigen-presentation-related gene such as Ctsf and inflammation, particularly for NF-κB signaling and complement cascades, underwent drastic changes in cardiac resident macrophages. GO cellular compartment analysis was also performed and showed specific organelle enrichment trends of the involved genes. Conclusion Dysregulated metabolism intertwines with inflammation in cardiac resident macrophages upon HFD feeding in mice, and further research on crosstalk among organelles could shed more light on potential mechanisms.